Implementasi Algoritma AES 128 Bit sebagai Pengaman Teks di Aplikasi Note Berbasis Android - Aji Permana; Elan Jaelani (JEJARING : Jurnal Teknologi dan Manajemen Informatika, 2020)
Abstract : In all spheres of life from all circles utilizing technology to exchange information. One of the media owned by a lot of people are mobile device, such as mobile phones and tablet computers, many people already use mobile devices for information exchange of messages of information. There are various kind of safety text in the note application, one of them by way of encrypting the note text. Encryption is the process of disguising the contents of the note text, so that unauthorized persons or even hacker can not know the contents of the note text. The encryption process create text notes in disguise their contents but still a form of writing therefore, although its text has been encrypted notes will still arouse suspicion so that occur in the aspects of information security, the security of various technique. Cryptography is a technique to hide so that people who are not interested or even eavesdroppers can not know the contents of the note text. This study discusses the implementation of Aes 128 bit algorithm for securing the text and the algorithm used is advanced encryption standard. This study aims to build application that can encrypt text and describe text which implemented on mobile devices android. The application is built using android studio. Based on the use of the application showed that text is encrypted with advanced encryption standard algorithm on mobile devices android can be described back in.Keywords : Cryptography, AES 128 bit algorithm, encryption, android.